Exploration of novel antimicrobials and comparative genomic analysis for the control of foodborne pathogens - Jia, Mo, author; Yang, Hua, advisor; Belk, Keith, committee member; Martin, Jennifer, committee member; Abdo, Zaid, committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.
Keywords: herb extract against foodborne pathogen; CRISPR-Cas9 antimicrobial; whole genome analysis